Performance Investigation of Low-Cost Dual-Axis Solar Tracker using Light Dependent Resistor - Chivorn Keo; Sarot Srang; Rattana Seng (Association for Scientific Computing Electronics and Engineering (ASCEE), 2023)
To generate power, the solar tracker mechanism can be mounted on a stationary or mobile platform. Moving platforms include boats, ground vehicles, and aerial vehicles. The solar tracker must be a mechanism that can keep the solar panel perpendicular to the direction of the sun at an appropriate level of precision in order to be more effective. Therefore, this research is going to investigate the performance of a low-cost dual-axis solar tracker (parallel mechanism) installed on a moving platform. This work describes the simulation and experiment of a dual-axis solar tracker that is mounted on a rotating support plate with rotational axis. This simulation uses the method of controlling linear actuators to adjust the solar panel perpendicular to the direction of sunlight. Both actuators were controlled by proportional and integral controllers (PI), which will make the system have a faster response time. The tracker is equipped with a type of low-cost sunlight sensor to provide the information for determining the orientation of the sunlight vector with respect to the solar panel. The sunlight sensor was designed and fabricated on our own by adding four light-dependent resistors in the four different quadrants. For the purpose of tracking the sun, the mathematical models of the tracker mechanism, sun sensor, and control architecture are defined. The results of simulation and experiment demonstrate that the tracker control system can follow the sun with some tracking error (about 2 degrees) at its final alignment. In real-time applications, solar trackers can be used on vehicles or boats to adjust solar panels on their surfaces and increase their exposure to sunlight and electrical output.